Exploring coaching and mentoring models for effective human resource development - Zainal Abiddin, Norhasni; Hassan, Aminuddin (The Journal of International Social Research, 2010)
There are various mentoring and coaching models. A mentoring/coaching model gives structure to mentoring/coaching. Models help to provide a framework for mentoring/coaching sessions. Different models provide alternative perspectives to help the mentee/coachee in a variety ways. It is a strategy that allows a mentor/coach, to help a mentees/coachees see a path to reach their goals. How to achieve results as a mentor/coach is increased by learning how to use one or more approaches/models. A mentoring/coaching model acts as a guideline. It is a strategic way to find solutions, change behaviors, get rid of limiting beliefs, achieve growth and reach the mentee/coachee goals. This article is designed to summarize existing literature on mentoring and coaching models in order to assist coach-coachee in enhancing the best practices in mentoring/coaching for effective human resource development.